2002
DOI: 10.1007/s1012601-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Stable Integration and Functional Expression of Flounder Growth Hormone Gene in Transformed Microalga, Chlorella ellipsoidea

Abstract: Chlorella is an attractive organism for complex recombinant protein production because of its eukaryotic characteristics and low cost for large-scale culture. Protoplasts of C. ellipsoidea were transformed with a vector containing the flounder growth hormone gene (fGH) under the control of the cauliflower mosaic virus 35S promoter, and the phleomycin resistance Sh ble gene under the control of the Chlamydomonas RBCS2 gene promoter. The presence of introduced DNA was first determined by PCR amplification of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 25 publications
3
69
0
1
Order By: Relevance
“…Cartilage is an avascular and relatively tumor-resistant tissue that is composed predominantly of proteoglycans, several types of collagen, and noncollagenous matrix proteins (1)(2)(3). The resistance of cartilage to capillary invasion has long been postulated to be a function of the presence of endogenous inhibitors of angiogenesis, which inhibit new blood vessel formation from pre-existing vessels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cartilage is an avascular and relatively tumor-resistant tissue that is composed predominantly of proteoglycans, several types of collagen, and noncollagenous matrix proteins (1)(2)(3). The resistance of cartilage to capillary invasion has long been postulated to be a function of the presence of endogenous inhibitors of angiogenesis, which inhibit new blood vessel formation from pre-existing vessels.…”
mentioning
confidence: 99%
“…The resistance of cartilage to capillary invasion has long been postulated to be a function of the presence of endogenous inhibitors of angiogenesis, which inhibit new blood vessel formation from pre-existing vessels. The first of these inhibitors purified to homogeneity was a cartilage-derived tissue inhibitor of metalloproteinases (TIMP), 2 a protein that was demonstrated to be a potent inhibitor of capillary EC proliferation and migration in vitro, and angiogenesis in vivo in both the chick chorioallantoic membrane (CAM) assay and the corneal pocket assay (4,5). Shortly thereafter, a chondrocyte-derived angiogenesis inhibitor, a 35.5-kDa protein isolated from chondrocyte primary cultures, was shown to inhibit angiogenesis in vitro in EC proliferation and migration assays and in vivo in the CAM assay (6).…”
mentioning
confidence: 99%
“…These results demonstrated that CAT was successfully expressed in the transformed Chlorella and functioned properly to exhibit chloramphenicol resistance. An overall efficiency for our transformation was estimated to be approximately one transgenic colony per 3000 Chlorella cells, relatively high compared with any C. vulgaris nuclear transformation system ever reported (Apt et al, 1996;Chen et al, 2001;Kim et al, 2002). …”
Section: Selection and Chloramphenicol Resistance Of Transgenic Chlormentioning
confidence: 86%
“…In another study, C. ellipsoidea was transformed with a vector containing the flounder growth hormone gene (fGH) under the control of the 35S promoter, and the phleomycin resistance Sh ble gene under the control of the Chlamydomonas RBCS2 gene promoter. Over 400 µg fGH protein expression per one liter of culture containing 1 x 10 8 cells/mL was estimated by ELISA (Kim et al, 2002). However, the expression levels of these foreign genes in transformed Chlorella were still relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…Des centaines de milliers d'espèces de microalgues sont réparties sur la surface du globe en milieu marin, dulçaquicole 4 ou saumâtre (Figures 1-4 Dans la liste des promoteurs utilisés chez les microalgues, on trouve le très classique promoteur du gène 35S du virus de la mosaïque du chou-fleur, utilisé avec succès chez Chlorella ellipsoidea [19]. A mentionner, le promoteur de nitrate reductase endogène, actif chez Chlamydomonas processus de glycosylation, en amont du point de divergence entre les plantes supérieures et les animaux.…”
Section: Les Microalguesunclassified